Dealing with bombs in rural exeter: global threat, local response - Ong, Weichong (2016)
The recent bomb attack on Exeter, England, demonstrated that global threats occur in centres of power as well as their peripheries. As such, an adequate local response and local leadership are crucial in both the prevention and 'firefighting' roles.